Aggregation behavior of nucleoside-boron cluster conjugates in aqueous solutions - Matejícek, Pavel (Langmuir : the ACS journal of surfaces and colloids, 2008)
We report the first evidence that boron-containing nucleoside conjugates have a tendency to associate in water solutions. The size, charge, and exoskeletal pattern of the boron cluster can strongly influence the aggregation. The aggregation of nucleosides with attached boron clusters was observed using light scattering and atomic force microscopy techniques. Although the species containing either the bulky amphiphilic [3-cobalt(III) bis(1,2-dicarbollide)]- anion or the electroneutral dicarba-closo-dodecaboranyl moiety tend to form stable nanoparticles in aqueous solutions, the compounds bearing the smaller, negatively charged dicarba-nido-undecaboranyl moiety as well as the unmodified nucleosides do not aggregate. The light scattering measurements also showed that the aggregated species can interact with nonionic surfactant Triton X-100 in solution. The partition coefficients P in the water-octanol system correlate fairly well with the aggregation tendency observed by light scattering measurements. This finding allows us to predict the association behavior of boron-cluster-containing nucleosides on a qualitative level. The observed phenomenon can contribute to a better understanding of biological properties of boronated nucleosides and the design of boronated nucleoside-based drugs such as boron carriers for boron neutron capture therapy of tumors (BNCT) and antiviral agents